2013
DOI: 10.1371/journal.pone.0068055
|View full text |Cite
|
Sign up to set email alerts
|

Tetanus Toxin Hc Fragment Induces the Formation of Ceramide Platforms and Protects Neuronal Cells against Oxidative Stress

Abstract: Tetanus toxin (TeTx) is the protein, synthesized by the anaerobic bacteria Clostridium tetani, which causes tetanus disease. TeTx gains entry into target cells by means of its interaction with lipid rafts, which are membrane domains enriched in sphingomyelin and cholesterol. However, the exact mechanism of host membrane binding remains to be fully established. In the present study we used the recombinant carboxyl terminal fragment from TeTx (Hc-TeTx), the domain responsible for target neuron binding, showing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 60 publications
1
14
0
Order By: Relevance
“…The breakdown of plasma membrane sphingomyelin or enrichment of the plasma membrane with ceramide increases proteolysis (in a mechanism also known as 'ectodomain shedding') of another TACE substrate, such as the interleukin-6 receptor (IL-6R) [46]. Thus, according to published data, a model in which the nSMase-activated TACE contributes to Akt activation arises, which is in agreement with the nSMase-dependent phosphorylation of Akt exerted by the BDNF action in CGN, shown in the present work, as well as in previous work from our group [42].…”
Section: (B) (A)supporting
confidence: 92%
See 3 more Smart Citations
“…The breakdown of plasma membrane sphingomyelin or enrichment of the plasma membrane with ceramide increases proteolysis (in a mechanism also known as 'ectodomain shedding') of another TACE substrate, such as the interleukin-6 receptor (IL-6R) [46]. Thus, according to published data, a model in which the nSMase-activated TACE contributes to Akt activation arises, which is in agreement with the nSMase-dependent phosphorylation of Akt exerted by the BDNF action in CGN, shown in the present work, as well as in previous work from our group [42].…”
Section: (B) (A)supporting
confidence: 92%
“…The increase in ceramide levels is supposed to change membrane configuration, increasing the content in ceramide platforms, which are considered to be a subset of the so‐called ‘lipid rafts’, which are membrane microdomains rich in cholesterol and sphingolipids. Recently, it has been demonstrated that the fragment Hc from tetanus toxin induces the formation of ceramide platforms and protects cells from oxidative stress in a nSMase‐dependent manner [42]. Regarding the role of SMase activity in cytoprotective outcome, some metabolites derived from sphingolipid processing have been involved in Akt signaling, pointing to S1P as a crucial effector molecule in some events leading to Akt activation [43].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several fusion proteins have been tested and reported to have some effects on neuronal cells, including Bcl-xL-TTC [116], BDNF-TTC [117], and GDNF-TTC [118]. However, the TTC delivery platform itself without a fusion cargo also stimulated signaling pathways [117, 119], which complicated the interpretation of the results.…”
Section: Current Antitoxins Against Botulismmentioning
confidence: 99%